A flonicamid and spirotetramat suspension concentrate formulation and a preparation method thereof
Patent Information
- Application Number
- CN202611134361.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]相关技术中氟啶虫酰胺与螺虫乙酯复配悬浮体系存在分散不均、泡沫偏高、贮存粒径增长、硬水稀释絮凝和再分散性下降的问题,为了改善这一缺陷,本申请提供一种氟啶虫酰胺与螺虫乙酯悬浮剂制剂及其制备方法
1、本申请通过在氟啶虫酰胺与螺虫乙酯高含量悬浮体系中配置改性纳米纤维素稳定剂和消泡界面调节组分,使分散稳定、粒径保持和泡沫调节在同一水悬浮体系中配合进行,有利于改善悬浮率、D90粒径、湿筛残余、持久泡沫量和贮存外观等制剂稳定性指标。
Abstract
Description
Technical Field
[0001] This application relates to the field of pesticide suspension technology, specifically to a suspension formulation of flonicamid and spirotetramat and its preparation method. Background Technology
[0002] Flupyradifurone and spirotetramat are both commonly used insecticidal active ingredients in agricultural production. Preparing different active ingredients into suspensions improves application convenience, reduces the use of organic solvents, and meets the needs of field spraying operations. Suspensions typically consist of the active ingredient, dispersing and wetting agents, stabilizers, antifreeze agents, preservatives, antifoaming components, and water. Their quality stability is closely related to the particle size, dispersion state, foam control, storage sedimentation, hard water dilution state, and redispersibility of the active ingredient.
[0003] In compound suspension concentrates with high active ingredient content, flonicamid and spirotetramat differ in crystal surface polarity, wetting rate, grinding stress, and tendency to re-agglomerate after refining. This can easily lead to problems such as uneven initial powder dispersion, increased foaming during sand milling, re-agglomeration of fine particles, and sedimentation or agglomeration after storage. In field application, suspension concentrates often need to be diluted with hard water. Calcium and magnesium ions in the water may compress the anionic dispersion layer or induce inter-particle bridging and flocculation, causing sedimentation of the diluted solution, increased coarse particle residue on sieves, and decreased spray uniformity. Commonly used dispersants and wetting agents and compound stabilizers can provide basic suspension capacity, but they cannot simultaneously address the initial wetting of both types of active ingredients, sand milling refinement, particle size retention during storage, and anti-flocculation capabilities with hard water dilution.
[0004] Regarding the aforementioned technologies, the inventors believe that although the existing suspension system of flupyradifurone and spirotetramat can achieve basic dispersion effects through ordinary dispersion stabilization systems, it is still prone to problems such as particle size increase, excessive foaming, sedimentation, and increased sieve residue under high content, sand milling, cold and hot storage, and hard water dilution scenarios, which in turn affect the stability of formulation processing and the uniformity of field dilution and application. Summary of the Invention
[0005] In related technologies, the suspension system of flonicamid and spirotetramat has problems such as uneven dispersion, high foaming, increased storage particle size, flocculation due to hard water dilution, and decreased redispersibility. In order to improve this defect, this application provides a flonicamid and spirotetramat suspension formulation and its preparation method.
[0006] In a first aspect, this application provides a suspension formulation of flonicamid and spirotetramat, employing the following technical solution: A suspension formulation of flonicamid and spirotetramat, by mass percentage, comprises 14-18% flonicamid, 20-28% spirotetramat, 5-10% dispersing and wetting agent, 0.5-2% auxiliary stabilizer, 0.2-2.5% modified nanocellulose stabilizer (based on effective solids), 3-7% antifreeze, 0.1-0.5% preservative, 0.05-0.8% defoaming interface regulating component, with the balance made up to 100% by water. The modified nanocellulose stabilizer is nanocellulose with both carboxyl and sulfonate groups on its surface.
[0007] By adopting the above technical solution, flonicamid and spirotetramat coexist in a high content in an aqueous suspension system. The dispersing and wetting agent improves the initial wetting and powder dispersion of the two types of active ingredients. The auxiliary stabilizer provides a basic stable environment in the continuous aqueous phase. The modified nanocellulose stabilizer uses nanocellulose as a skeleton and has carboxyl and sulfonate groups on its surface. The nanocellulose skeleton helps to increase the spatial spacing between the active ingredient particles and provide weak network support. The carboxyl and sulfonate groups help to form a hydrated ion layer and compensate for the difference in interfacial stability between flonicamid and spirotetramat. The defoaming interface regulating component participates in the gas-liquid interface regulation during sand milling and storage. After the above components are combined, it helps to reduce the risk of agglomeration, sedimentation, particle size increase and foam accumulation caused by the different surface polarity, wetting speed and grinding stress of the two active ingredients. This makes the suspension maintain a relatively stable formulation state in terms of particle size, suspension rate, wet sieve residue, persistent foam amount, hard water dilution state and cold and hot storage stability.
[0008] Preferably, the dispersing and wetting agent includes an amphiphilic carboxylic acid-sulfonate comb-shaped dispersant, which is a water-dispersible polymer formed by copolymerization of a carboxyl-containing alkenyl monomer or its salt, an alkenyl monomer containing a sulfonate group, a polyether side chain monomer, and a hydrophobic anchoring monomer.
[0009] By adopting the above technical solution, the amphiphilic carboxylic acid-sulfonate comb-shaped dispersant enters the system as part of the dispersing and wetting agent. The hydrophobic anchoring structure improves its adsorption stability on the surface of flonicamid and spirotetramat technical particles. The carboxylate and sulfonate structures facilitate the formation of an ionization layer on the outer side of the particles, while the polyether side chain structure facilitates the formation of hydration steric hindrance. The combination of hydrophobic anchoring, the carboxylate / sulfonate ionization layer, and the polyether hydration steric hindrance improves the wetting and adsorption of the two technical particles and maintains particle size after milling, reducing the risk of fine particle re-aggregation after milling.
[0010] Preferably, when preparing the amphiphilic carboxylic acid-sulfonate comb-shaped dispersant, the molar ratio of the carboxyl-containing alkenyl monomer or its salt, the alkenyl monomer containing sulfonate groups, the polyether side chain monomer, and the hydrophobic anchoring monomer is 1:(0.2-1.5):(0.5-3):(0.05-0.8).
[0011] By adopting the above technical solution, the functional monomers are combined according to the above molar ratio during preparation, which is conducive to the formation of a comb-shaped polymer with a combination of carboxylate structure, sulfonate structure, polyether side chain structure and hydrophobic anchoring structure in the resulting dispersant, thereby taking into account the adsorption on the surface of the active ingredient crystal, the dispersion in the aqueous phase and the steric hindrance of hydration.
[0012] Preferably, the modified nanocellulose stabilizer is prepared by the following method: (1) Nanocellulose is oxidized by TEMPO or carboxymethylated to obtain carboxylated nanocellulose; (2) Disperse the carboxylated nanocellulose in water, purge it with an inert gas, add a persulfate initiator and an alkenyl monomer containing a sulfonate group, and carry out graft polymerization at 60-70°C for 3-5 hours; (3) After grafting polymerization, the modified nanocellulose stabilizer is obtained by centrifugation, washing, ultrafiltration or dialysis, and adjustment of solid content.
[0013] By employing the above technical solution, the nanocellulose is first carboxylated to provide hydrophilic carboxyl sites for the nanocellulose framework. Then, under inert gas protection, the persulfate initiator, carboxylated nanocellulose, and alkenyl monomers containing sulfonate groups are placed together in graft polymerization conditions, allowing the sulfonate structure to be introduced into the nanocellulose system during polymerization. After washing, ultrafiltration, or dialysis to remove unreacted monomers and free small molecules, the resulting stabilizer possesses a nanocellulose framework, carboxyl hydration sites, and sulfonate ionization sites, which helps reduce the risks of re-agglomeration after milling, storage sedimentation, and particle size increase.
[0014] Preferably, the alkenyl monomer containing sulfonate groups includes one or more of 2-acrylamido-2-methylpropanesulfonate, vinyl sulfonate, and styrene sulfonate.
[0015] By adopting the above technical solution, alkenyl monomers containing sulfonate groups can introduce a strong hydrophilic ionic structure into modified nanocellulose stabilizers. Different alkenyl monomers have differences in polymerization activity, chain segment flexibility and hydration ability, which can provide adjustment leeway for suspending agents with different active ingredient contents and different viscosity windows.
[0016] Preferably, the defoaming interface regulating component includes aminosilane-modified silica and polyether-modified siloxane, wherein the mass ratio of aminosilane-modified silica to polyether-modified siloxane is 1:(0.3-3).
[0017] By adopting the above technical solution, aminosilane-modified silica can provide an inorganic particle interface with surface modification, and polyether-modified siloxane can regulate the foam behavior during the milling and dispersion process. When the two are combined in the above proportion, it is beneficial to reduce the persistent foam generated during shearing and milling processes, and also to reduce the risk of local precipitation or floating of single siloxane components in the aqueous suspension system.
[0018] Preferably, the defoaming interface regulating component is prepared by the following method: (1) Surface treatment of silica with aminosilane to obtain aminosilane modified silica; wherein the aminosilane includes one or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and N-aminoethyl-3-aminopropyltrimethoxysilane; (2) The aminosilane-modified silica and polyether-modified siloxane are mixed and dispersed to obtain the defoaming interface regulating component.
[0019] By adopting the above technical solution, the surface of the silica is first treated with aminosilane to form an interface state that is more suitable for dispersion and coordination with polyether-modified siloxane. After mixing with polyether-modified siloxane, it enters the suspension system, which helps to improve the compatibility of inorganic particles and siloxane components in the aqueous phase and reduce foaming during the grinding process and interface separation during the storage process.
[0020] Preferably, the auxiliary stabilizer includes a hard water-dilutable anti-flocculation crosslinking polymer stabilizer, wherein the hard water-dilutable anti-flocculation crosslinking polymer stabilizer is a water-dispersible crosslinking polymer containing carboxylate structural units, sulfonate structural units, and polycarboxyl structural units formed from polymerizable monomers containing polycarboxyl groups.
[0021] By adopting the above technical solution, the hard water-diluted anti-flocculation cross-linked polymer stabilizer is incorporated into the suspension formulation system as part of the auxiliary stabilizer. The carboxylate structure, sulfonate structure, and polycarboxyl group structure in the cross-linked polymer can regulate the ionic environment after hard water dilution. The cross-linking structure helps to limit the excessive extension or entanglement of polymer chain segments, thereby reducing the compression and bridging effect of calcium and magnesium ions on the dispersion layer of the active pharmaceutical ingredient.
[0022] Preferably, the hard water dilution anti-flocculation crosslinking polymer stabilizer is prepared by the following method: (1) Disperse carboxyl-containing alkenyl monomers or their salts, alkenyl monomers containing sulfonate groups, polymerizable monomers containing multiple carboxyl groups, and crosslinking monomers in water to obtain an aqueous monomer phase; (2) Under inert gas protection, a persulfate-bisulfite redox initiation system is added to the aqueous phase of the monomer and reacted at 35-60℃ for 2-5 hours. The mixture is then filtered through a 100μm filter and the effective solid content of the crosslinked polymer is adjusted to obtain the hard water diluted antiflocculation crosslinked polymer stabilizer.
[0023] By adopting the above technical solution, alkenyl monomers containing carboxyl groups or their salts, alkenyl monomers containing sulfonate groups and polymerizable monomers containing multiple carboxyl groups are copolymerized in the presence of crosslinking monomers, so that carboxylate structure, sulfonate structure, multiple carboxyl group structure and crosslinking structure coexist in water-dispersible polymers. This is beneficial for regulating the interaction between calcium and magnesium ions and anionic structures in hard water dilution environment and reducing the flocculation of active pharmaceutical ingredient particles.
[0024] Secondly, this application provides a method for preparing a suspension formulation of flonicamid and spirotetramat, using the following technical solution: A method for preparing a suspension formulation of flonicamid and spirotetramat according to any one of the above-mentioned methods is characterized by comprising the following steps: (1) Water, dispersant, wetting agent, auxiliary stabilizer, antifreeze agent and modified nanocellulose stabilizer are mixed to obtain a dispersed and stable aqueous phase; (2) Flupyradifurone technical and spirotetramat technical were added to the dispersed and stable aqueous phase under stirring conditions, and shear dispersion was carried out to obtain a pre-dispersed slurry; (3) The pre-dispersed slurry is subjected to sand milling, preservatives and defoaming interface conditioning components are added, and water is added to make up the difference, so as to obtain the flonicamid and spirotetramat suspension preparation.
[0025] By adopting the above technical solution, the dispersant, wetting agent, auxiliary stabilizer, antifreeze agent, and modified nanocellulose stabilizer are first dispersed and stabilized in water to form a stable aqueous phase. Then, flonicamid technical and spirotetramat technical are added for shear dispersion, which allows the technical powder to enter an aqueous phase environment that already has wetting and stabilizing capabilities, reducing the risk of initial powder agglomeration and the formation of local high-concentration agglomerates. Subsequently, sand milling and the addition of preservatives and defoaming interface conditioning components can further adjust the interface and foam state after particle size refinement, thereby helping to obtain a formulation with particle size, wet sieve residue, hard water dilution state, and storage stability that meet the requirements of suspension concentrates.
[0026] In summary, this application has the following beneficial effects: 1. This application, by configuring a modified nanocellulose stabilizer and an antifoaming interface regulating component in a high-content suspension system of flonicamid and spirotetramat, enables dispersion stability, particle size maintenance and foam regulation to be carried out in the same aqueous suspension system, which is beneficial to improving formulation stability indicators such as suspension rate, D90 particle size, wet sieve residue, persistent foam amount and storage appearance.
[0027] 2. This application further configures an amphiphilic carboxylic acid-sulfonate comb-shaped dispersant and a hard water dilution anti-flocculation crosslinking polymer stabilizer, so that the restrictive effects of hydrophobic anchoring, carboxylic acid / sulfonate ionization, polyether hydration steric hindrance, multi-carboxyl group structure and crosslinking structure on polymer chain segment movement correspond to particle wetting adsorption and hard water dilution anti-flocculation process, respectively. This is beneficial to improve the particle size retention ability after sand milling and reduce the D90 growth rate, sedimentation state and 75μm sieve residue after hard water dilution, thereby improving the formulation performance during the dilution and use stage.
[0028] 3. This application, by first constructing a stable aqueous phase and then adding two active ingredients for shear dispersion and sand milling, ensures that the active ingredient powder is in a wetted and stable environment before entering the high-shear and sand milling stages, which is beneficial to improving the pre-dispersion uniformity and the stability of sand milling particle size control. Detailed Implementation
[0029] The following detailed description, in conjunction with specific examples, further illustrates this application. Flupyradifurone and spirotetramat technicals are pesticide formulation technicals. The common polycarboxylate-type dispersant and wetting agent is a sodium polyacrylate-type solid dispersant with an active ingredient content of not less than 95% and a number-average molecular weight of 5000-8000. The common nonionic-anionic composite stabilizer is a compound formed by hydroxyethyl cellulose and sodium carboxymethyl cellulose in a 2:1 mass ratio. The antifreeze agent is ethylene glycol, and the preservative is 1,2-benzisothiazolin-3-one. The nanocellulose is a cellulose nanofiber aqueous dispersion with a dry basis solid content of 2.0%, an average diameter of 20-80 nm, and a length of 0.5-5 μm. The feed amount is calculated based on dry basis mass. The unmodified nanocellulose used in the comparative example is a 10.0% unmodified nanocellulose concentrate obtained by concentrating the above-mentioned cellulose nanofiber aqueous dispersion. The nano-silica uses hydrophilic fumed silica with an average native particle size of 7-20 nm and a specific surface area of 150-250 m² / g. The polyether-modified siloxane uses a water-based pesticide suspension dispersible polyether-modified organosilicon material with an effective component content of 80% and a viscosity of 300-1200 mPa·s at 25℃. 2-Acrylamide-2-methylpropanesulfonate is sodium 2-acrylamide-2-methylpropanesulfonate, vinyl sulfonate is sodium vinyl sulfonate, and styrene sulfonate is sodium p-styrene sulfonate. Disodium maleate is prepared by hydrolysis of maleic anhydride followed by complete neutralization with sodium hydroxide. The number average molecular weight of methoxy polyethylene glycol methacrylate is 1000, and the number average molecular weight of allyl polyoxyethylene ether is 1000. FR-35 is a lignin sulfonate-naphthalene sulfonate composite anionic dispersant and wetting agent with a solid content of 35%; 8070 is a polycarboxylate-type water dispersant with a solid content of 70%. Conventional silicone defoamers are polydimethylsiloxane emulsion defoamers with an active ingredient content of 30% and are in water-dispersible form.
[0030] When the self-made dispersant, modified nanocellulose stabilizer, and hard water-diluted anti-flocculation crosslinking polymer stabilizer are added in the form of dispersions or concentrated dispersions, their dosage is calculated based on the effective solid mass. The actual amount added is calculated by dividing the effective solid mass by the solid content of the dispersion or concentrated dispersion. The amount of water added is the difference between the actual amount added and the effective solid mass. The additional amount of water added is the difference between the total water volume of the formulation and the amount of water added by each dispersion or concentrated dispersion.
[0031] Preparation example of modified nanocellulose stabilizer Preparation Example 1 (1) 10.0 g of cellulose nanofibers on a dry basis were dispersed in deionized water, and TEMPO, sodium bromide and sodium hypochlorite solutions were added. The pH of the system was maintained at 10.0 with sodium hydroxide solution at 20 °C. After reacting for 3.0 h, ethanol was added to terminate the reaction. The mixture was centrifuged and washed until the washing solution was close to neutral to obtain carboxylated cellulose nanofibers.
[0032] (2) The obtained carboxylated nanocellulose was dispersed in deionized water, the dry basis mass fraction of nanocellulose was adjusted to 1.0%, the pH of the system was adjusted to 7.0-8.0, nitrogen gas was purged for 30 min, ammonium persulfate and sodium 2-acrylamide-2-methylpropanesulfonate were added, and graft polymerization was carried out at 60℃ for 3.0 h.
[0033] (3) After graft polymerization, the mixture was centrifuged, washed, and ultrafiltered to remove unreacted monomers and free small molecules, and then concentrated to a solid content of 10.0% to obtain a concentrated dispersion of modified nanocellulose stabilizer. The infrared spectrum of the obtained modified nanocellulose stabilizer showed an absorption signal related to the sulfonate structure, and elemental analysis detected sulfur.
[0034] Preparation Examples 2-4 Preparation Examples 2-4 were prepared according to the method of Preparation Example 1, with the difference being that the carboxylation treatment conditions, the type and amount of alkenyl monomers containing sulfonate groups, the amount of initiator, the graft polymerization temperature, and the graft polymerization time were set according to Tables 1-1 and 1-2; after graft polymerization, all were subjected to centrifugation, washing, and ultrafiltration, and concentrated to the solid content shown in Table 1-3.
[0035] Preparation Example 5 10.0 g of cellulose nanofibers (dry basis) were dispersed in 500.0 g of isopropanol-water mixture (mass ratio of isopropanol to water: 80:20). Sodium hydroxide was added for alkalization treatment for 1.0 h, followed by the addition of sodium chloroacetate. The reaction was carried out at 60 °C for 4.0 h. After the reaction, the nanofibers were washed with an ethanol-water solution until neutral to obtain carboxymethylated cellulose nanofibers. This carboxymethylated cellulose nanofibers were dispersed in water, and the dry basis mass fraction of the nanofibers was adjusted to 1.0%. Nitrogen gas was purged, and ammonium persulfate and sodium p-styrene sulfonate were added. Graft polymerization was carried out at 70 °C for 5.0 h. After graft polymerization, the nanofibers were centrifuged, washed, and dialyzed, and then concentrated to a solid content of 10.0% to obtain a concentrated dispersion of modified cellulose nanofiber stabilizer.
[0036] Table 1-1 Carboxylation conditions for the preparation examples of modified nanocellulose stabilizers Preparation Example 1 10.0 TEMPO oxidation TEMPO 0.16g, NaBr 1.0g, NaClO available chlorine 4.8mmol / g dry cellulose 20 3.0 Preparation Example 2 10.0 TEMPO oxidation TEMPO 0.16g, NaBr 1.0g, NaClO available chlorine 5.6mmol / g dry cellulose 20 3.5 Preparation Example 3 10.0 TEMPO oxidation TEMPO 0.18g, NaBr 1.2g, NaClO available chlorine 6.2mmol / g dry cellulose 25 4.0 Preparation Example 4 10.0 TEMPO oxidation TEMPO 0.14g, NaBr 0.9g, NaClO available chlorine 5.0mmol / g dry cellulose 20 3.0 Preparation Example 5 10.0 Carboxymethylation 8.0g NaOH, 10.0g sodium chloroacetate 60 4.0 Table 1-2 Graft polymerization conditions for the preparation examples of modified nanocellulose stabilizers Preparation Example 1 Sodium 2-acrylamide-2-methylpropanesulfonate 2.0 0.10 60 3.0 Preparation Example 2 Sodium 2-acrylamide-2-methylpropanesulfonate 6.0 0.18 62.5 3.5 Preparation Example 3 Sodium 2-acrylamide-2-methylpropanesulfonate 10.0 0.25 65 4.0 Preparation Example 4 Sodium vinyl sulfonate 8.0 0.22 67.5 4.5 Preparation Example 5 Sodium p-styrene sulfonate 15.0 0.30 70 5.0 Table 1-3 Product parameters of the preparation examples of modified nanocellulose stabilizers Preparation Example 1 1.25 0.42 10.0 Preparation Example 2 1.38 0.91 10.0 Preparation Example 3 1.52 1.36 10.0 Preparation Example 4 1.19 0.88 10.0 Preparation Example 5 1.10 1.22 10.0
[0037] Preparation example of defoaming interface conditioning components Preparation Example 6 20.0 g of hydrophilic fumed silica was dispersed in 180.0 g of ethanol-water solution. The pH of the system was adjusted, and 2.0 g of aminosilane was added. The mixture was stirred at 50 °C for 2 h, filtered, and washed with ethanol-water solution until the filtrate had almost no free silane odor. The filtrate was dried at 80 °C for 6 h to obtain aminosilane-modified silica. Then, 10.0 g of the aminosilane-modified silica was mixed with polyether-modified siloxane and homogenized to obtain the defoaming interface regulating component. The key variables in preparation examples 6-8 are shown in Table 2.
[0038] Table 2 Key variables in the preparation examples of defoaming interface conditioning components Preparation Example 6 3-Aminopropyltriethoxysilane 80:20 8.5 3.0 6000r / min, 10min Preparation Example 7 3-Aminopropyltriethoxysilane 80:20 8.5 10.0 6000r / min, 10min Preparation Example 8 3-Aminopropyltrimethoxysilane 75:25 8.0 30.0 8000r / min, 8min
[0039] Preparation example of amphiphilic carboxylic acid-sulfonate comb-shaped dispersants Preparation Example 9 Following the feeding instructions in Tables 3-1 and 3-2, alkenyl monomers containing carboxyl groups or their salts, alkenyl monomers containing sulfonate groups, polyether side-chain monomers, and hydrophobic anchoring monomers were added to a mixed solvent of deionized water and isopropanol. The pH was adjusted to 7.0-8.0, and after nitrogen purging, ammonium persulfate was added. The reaction was carried out at 70°C for 4 hours. Subsequently, isopropanol was removed under reduced pressure and water was added to obtain an amphiphilic carboxylic acid-sulfonate comb-shaped dispersant. Preparation Examples 10-11 were prepared using the same method. The purity of sodium acrylate, sodium 2-acrylamido-2-methylpropanesulfonate, styrene, disodium maleate, sodium vinyl sulfonate, and lauryl methacrylate was not less than 98%; the effective component content of methoxy polyethylene glycol methacrylate and allyl polyoxyethylene ether was not less than 95%, and the number average molecular weight of both was 1000. When calculating the molar ratio of the feed, one polyether macromonomer molecule was counted as one polyether side-chain monomer molar unit. When using the dispersant in the examples, the effective solid mass is used as the basis for calculation.
[0040] Table 3-1 Monomer Feeding Examples for the Preparation of Amphiphilic Carboxylic Acid-Sulfonate Comb Dispersants Preparation Example 9 Sodium acrylate 4.70 Sodium 2-acrylamide-2-methylpropanesulfonate 2.29 Methoxylated polyethylene glycol methacrylate 25.0 Styrene 0.26 1:0.2:0.5:0.05 Preparation Example 10 Sodium acrylate 4.70 Sodium 2-acrylamide-2-methylpropanesulfonate 9.17 Methoxylated polyethylene glycol methacrylate 75.0 Styrene 1.56 1:0.8:1.5:0.3 Preparation Example 11 Disodium maleate 8.00 Sodium vinyl sulfonate 9.75 Allyl polyoxyethylene ether 150.0 Lauryl methacrylate 10.15 1:1.5:3.0:0.8 Table 3-2 Reaction media and finished product parameters for the preparation example of amphiphilic carboxylic acid-sulfonate comb-shaped dispersants Preparation Example 9 95.0 25.0 0.32 30.0 Preparation Example 10 210.0 55.0 0.90 30.0 Preparation Example 11 415.0 105.0 1.78 30.0
[0041] Example of preparing an anti-flocculation crosslinking polymer stabilizer diluted with hard water Preparation Example 12 Carboxyl-containing alkenyl monomers or their salts, alkenyl monomers containing sulfonate groups, polymerizable monomers containing multiple carboxyl groups, and crosslinking monomers were added to the deionized water in the actual amounts shown in Table 4-1. The total monomer mass fraction in Table 4-1 was calculated as the percentage of the sum of the masses of the above four types of monomers and crosslinking monomers to the sum of their masses and the mass of deionized water used for polymerization. After purging with nitrogen for 30 min, the ammonium persulfate-sodium bisulfite redox initiation system was added dropwise, and the reaction was carried out at the temperature shown in Table 4-2. After the reaction, the mixture was filtered through a 100 μm filter, and deionized water was added again in the amounts shown in Table 4-2 to adjust the effective solids content of the crosslinked polymer to 10.0%, thus obtaining a hard water diluted anti-flocculation crosslinked polymer stabilizer. Preparation Examples 13-14 were prepared using the same method, with specific feeding and reaction conditions shown in Tables 4-1 and 4-2.
[0042] Table 4-1 Monomer Feeding Examples for Hard Water Dilution Antiflocculation Crosslinking Polymer Stabilizer Preparation Preparation Example 12 Sodium acrylate 6.0 Sodium 2-acrylamide-2-methylpropanesulfonate 4.0 Sodium itaconic acid 2.0 N,N'-Methylenebisacrylamide 0.08 Ammonium persulfate 0.12g + Sodium bisulfite 0.04g Preparation Example 13 Sodium acrylate 5.0 Sodium 2-acrylamide-2-methylpropanesulfonate 5.0 Sodium itaconic acid 3.0 N,N'-Methylenebisacrylamide 0.12 Ammonium persulfate 0.15 + Sodium bisulfite 0.05 Preparation Example 14 Sodium methacrylate 5.5 Sodium 2-acrylamide-2-methylpropanesulfonate 4.5 Disodium maleate 2.5 N,N'-Methylenebisacrylamide 0.16 Ammonium persulfate 0.18 + Sodium bisulfite 0.06 Table 4-2 Water quantity and reaction conditions in the preparation example of hard water dilution of antiflocculation crosslinking polymer stabilizer Preparation Example 12 12.0 88.59 19.97 450 35 5 10.0 Preparation Example 13 12.5 91.84 26.04 500 45 3 10.0 Preparation Example 14 13.0 84.72 28.98 550 60 2 10.0 Examples 1-5 Example 1
[0043] This embodiment provides a suspension formulation of flonicamid and spirotetramat. Based on 500.0g, its raw material composition is: flonicamid 70.0g, spirotetramat 100.0g, dispersant and wetting agent 25.0g, auxiliary stabilizer 2.5g, modified nanocellulose stabilizer effective solids 1.0g, antifreeze 15.0g, preservative 0.5g, and defoaming interface conditioning component obtained in Preparation Example 6 0.25g. The total water content of the formulation is 285.75g. 10.0g of the modified nanocellulose stabilizer concentrated dispersion obtained in Preparation Example 1 with a solid content of 10.0% was actually weighed, containing 1.0g of modified nanocellulose stabilizer effective solids and 9.0g of water; an additional 276.75g of water was added, bringing the total water content of the formulation to 285.75g, and the total feed mass to 500.0g.
[0044] Converted to mass percentage, this suspension formulation comprises 14.0% flonicamid, 20.0% spirotetramat, 5.0% dispersant and wetting agent, 0.5% auxiliary stabilizer, 0.2% modified nanocellulose stabilizer (based on effective solids), 3.0% antifreeze, 0.1% preservative, and 0.05% defoaming interface conditioning component, with the balance made up to 100% by water. The preparation method of this suspension formulation includes the following steps: (1) Take a portion of water, add a dispersing wetting agent, an auxiliary stabilizer, an antifreeze agent and the modified nanocellulose stabilizer obtained in Preparation Example 1, stir and mix to obtain a dispersed and stable aqueous phase; (2) Add flupyradifurone technical and spirotetramat technical to the dispersed and stable aqueous phase under stirring conditions, and shear and disperse at 1000 r / min for 60 min to obtain a pre-dispersed slurry; (3) The pre-dispersed slurry was subjected to sand milling, and preservatives and the defoaming interface conditioning component obtained in Preparation Example 6 were added, and water was added to make up to 500.0g to obtain the flonicamid and spirotetramat suspension preparation.
[0045] Examples 2-5 The difference between Examples 2-5 and Example 1 is that the feed amounts are set according to Table 5; the rest of the preparation methods are the same as in Example 1. Table 5 also lists the feed amounts for Example 1. The amounts of modified nanocellulose stabilizer listed in Table 5 are all based on effective solids, and the water content in the table is the total water content in the formulation. In actual preparation, the actual amount added is calculated based on the solid content of the concentrated dispersion of the modified nanocellulose stabilizer, and the water content introduced by the concentrated dispersion is deducted from the total water content of the formulation; the corresponding actual measurement conversion is shown in Table 5-1. Following the above feed and preparation methods, the flonicamid and spirotetramat suspension formulations were obtained respectively.
[0046] Table 5. Ingredient dosages for Examples 1-5 Example 1 70.0 100.0 25.0 2.5 1.0 15.0 0.5 0.25 285.75 Example 2 75.0 110.0 30.0 4.0 3.0 20.0 1.0 0.75 256.25 Example 3 80.0 120.0 40.0 6.0 6.0 25.0 1.5 1.5 220.0 Example 4 85.0 130.0 45.0 8.0 9.0 30.0 2.0 2.5 188.5 Example 5 90.0 140.0 50.0 10.0 12.5 35.0 2.5 4.0 156.0 Table 5-1 Actual stoichiometric conversion of the modified nanocellulose stabilizer concentrated dispersions in Examples 1-5 Example 1 1.0 10.0 9.0 276.75 Example 2 3.0 30.0 27.0 229.25 Example 3 6.0 60.0 54.0 166.0 Example 4 9.0 90.0 81.0 107.5 Example 5 12.5 125.0 112.5 43.5 Examples 6-9 Examples 6-9 differed from Example 3 in the source of the modified nanocellulose stabilizer, with an effective solid content of 6.0 g for each sample. 60.0 g of the 10.0% concentrated dispersion obtained in the corresponding preparation example was added to each sample, with 54.0 g of water incorporated into the concentrated dispersion, and an additional 166.0 g of water added. Table 6 lists Example 3 as the basis for performance comparison; the remaining raw materials and preparation steps were the same as in Example 3, yielding the flonicamid and spirotetramat suspension formulations, respectively.
[0047] Table 6. Sources of modified nanocellulose stabilizers in Examples 3 and 6-9 Example 3 Preparation Example 1 Example 6 Preparation Example 2 Example 7 Preparation Example 3 Example 8 Preparation Example 4 Example 9 Preparation Example 5 Examples 10-11 Examples 10-11 differed from Example 7 in the source of the defoaming interface regulating component, with each example using 1.5g of the component. Table 7 lists Example 7 as the basis for performance comparison. Each sample actually added 60.0g of the concentrated dispersion of 10.0% modified nanocellulose stabilizer obtained in Preparation Example 3, which carried 54.0g of water. An additional 166.0g of water was added. The remaining raw materials and preparation steps were the same as in Example 7, resulting in the flonicamid and spirotetramat suspension formulations.
[0048] Table 7. Sources of defoaming interface conditioning components in Examples 7 and 10-11 Example 7 Preparation Example 6 Example 10 Preparation Example 7 Example 11 Preparation Example 8 Examples 12-14 The difference between Example 12 and Example 11 is that the modified nanocellulose stabilizer pre-dispersion liquid solid content is 3%, the shearing speed is 3000 r / min, and the shearing time is 30 min; the difference between Examples 13-14 and Example 12 is only that the modified nanocellulose stabilizer pre-dispersion liquid solid content is 5% and 8%, respectively. The effective solid content of the modified nanocellulose stabilizer is 6.0 g in all examples, the defoaming interface regulating component is from Preparation Example 8, and the sand milling endpoint is D90 not greater than 5 μm in all examples. See Table 8 for details. The total feed mass of each sample is 500.0 g, and the flonicamid and spirotetramat suspension formulations are obtained respectively.
[0049] Table 8. Pre-dispersed liquid-solid content and mass balance of Examples 12-14 Example 12 3 200.0 194.0 26.0 Example 13 5 120.0 114.0 106.0 Example 14 8 75.0 69.0 151.0 Examples 15-17 Examples 15-17, based on Example 13, replaced 1.5g of ordinary polycarboxylate-type dispersing and wetting agent with 1.5g of amphiphilic carboxylic acid-sulfonate comb-shaped dispersing agent obtained from different preparation examples. The total mass of dispersing and wetting agent (excluding water contained in the self-made dispersing agent dispersion) was maintained at 40.0g. The defoaming interface conditioning component was sourced from Preparation Example 8. Each sample actually added 5.0g of 30.0% comb-shaped dispersing agent dispersion, which carried in 3.5g of water; simultaneously, 120.0g of 5.0% modified nanocellulose stabilizer pre-dispersion was added, which carried in 114.0g of water, and an additional 102.5g of water was added. Table 9 lists Example 13 as a comparative basis; the remaining raw materials and preparation steps were the same as in Example 13, respectively obtaining the flonicamid and spirotetramat suspension formulations.
[0050] Table 9. Sources and actual quantities of the amphiphilic carboxylic acid-sulfonate comb-shaped dispersants in Examples 13 and 15-17 Example 13 Not joined 0 0 0 106.0 Example 15 Preparation Example 9 1.5 5.0 3.5 102.5 Example 16 Preparation Example 10 1.5 5.0 3.5 102.5 Example 17 Preparation Example 11 1.5 5.0 3.5 102.5 Examples 18-20 Examples 18-20, based on Example 16, replaced 1.0g of the ordinary nonionic-anionic composite stabilizer in the auxiliary stabilizer with 1.0g of hard water-diluted antiflocculation crosslinking polymer stabilizer obtained from different preparation examples. The total effective component of the auxiliary stabilizer was maintained at 6.0g, and the amphiphilic carboxylic acid-sulfonate comb-shaped dispersant in the dispersing and wetting agent was sourced from Preparation Example 10. Each sample actually added 10.0g of stabilizer dispersion with an effective crosslinking polymer content of 10.0%, which carried in 9.0g of water; simultaneously, 120.0g of 5.0% modified nanocellulose stabilizer pre-dispersion was added, which carried in 114.0g of water, and 5.0g of 30.0% comb-shaped dispersant dispersion was added, which carried in 3.5g of water, plus an additional 93.5g of water. Table 10 lists Example 16 as a comparative basis; the remaining raw materials and preparation steps were the same as in Example 16, respectively obtaining the flonicamid and spirotetramat suspension formulations.
[0051] Table 10. Sources and actual quantities of crosslinking polymer stabilizers in Examples 16 and 18-20 Example 16 Not joined 0 0 0 102.5 Example 18 Preparation Example 12 1.0 10.0 9.0 93.5 Example 19 Preparation Example 13 1.0 10.0 9.0 93.5 Example 20 Preparation Example 14 1.0 10.0 9.0 93.5 Comparative Examples 1-4 Comparative Example 1 The difference between Comparative Example 1 and Example 3 is that no modified nanocellulose stabilizer was added, and water was added to make up to 500.0g; the other raw materials and preparation steps were the same as in Example 3.
[0052] Comparative Example 2 The difference between Comparative Example 2 and Example 3 is that 6.0g of dry-based unmodified nanocellulose was used instead of 6.0g of modified nanocellulose stabilizer effective solid, and 60.0g of unmodified nanocellulose concentrate with a solid content of 10.0% was actually added. The concentrate carried 54.0g of water, and an additional 166.0g of water was added. The remaining raw materials and preparation steps were the same as in Example 3.
[0053] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that no defoaming interface conditioning component was added, and water was added to make up to 500.0g; the other raw materials and preparation steps were the same as in Example 3.
[0054] Comparative Example 4 Comparative Example 4 used a common dispersion stabilization system. Based on 500.0g, the following were added: 80.0g of flonicamid, 120.0g of spirotetramat, 30.0g of FR-35 dispersant / wetting agent, 15.0g of 8070 dispersant / wetting agent, 20.0g of ethylene glycol, 0.75g of xanthan gum, 3.0g of magnesium aluminum silicate, 1.5g of preservative, 1.5g of conventional organosilicon defoamer, and 228.25g of water. During preparation, water, FR-35 dispersant / wetting agent, 8070 dispersant / wetting agent, ethylene glycol, xanthan gum, and magnesium aluminum silicate were mixed, and then the two technical materials were added. After shear dispersion and sand milling, the preservative and conventional organosilicon defoamer were added to obtain a flonicamid / spirotetramat suspension formulation.
[0055] Performance testing methods Three parallel samples were set up for each test item, and the results were taken as the arithmetic mean.
[0056] Except for the hard water dilution stability test, the standard water is standard hard water with a hardness of 342 mg / L based on calcium carbonate; the hard water dilution stability test uses standard hard water with a hardness of 500 mg / L based on calcium carbonate.
[0057] Active ingredient content test: Weigh 0.10 g of sample, dissolve in acetonitrile and dilute to 100 mL. After filtration through a 0.45 μm organic filter membrane, determine the contents of flonicamid and spirotetramat by high performance liquid chromatography (HPLC). The chromatographic column used was a C18 column (4.6 mm × 250 mm, 5 μm). The mobile phase was acetonitrile-water (70:30 v / v), the flow rate was 1.0 mL / min, the column temperature was 30 ℃, the detection wavelength was 270 nm, and the injection volume was 10 μL.
[0058] pH test: The pH value of the original solution was directly measured at 20±2℃. Each sample was measured 3 times and the average value was taken.
[0059] Particle size test: Dilute the sample with deionized water to a concentration suitable for laser particle size analyzer measurement, gently stir to disperse, do not use long-term sonication which will continue to damage the particle state, measure 3 times consecutively and take the average value, the result is expressed as D90.
[0060] Suspension rate test: Add 1.0g of sample to standard water to prepare 250mL of test solution. After thorough shaking, let stand at 25℃ for 30min. Take the upper 9 / 10 volume of suspension and determine the mass of flonicamid and spirotetramat separately. The sum of their masses is taken as the mass of the active ingredient in the upper suspension. The sum of the masses of the two active ingredients in the original test solution is taken as the total mass of the active ingredients. Calculate the suspension rate using the following formula: Suspension rate / % = Mass of effective components in the upper 9 / 10 volume of suspension ÷ (Total mass of effective components added to the test solution × 0.9) × 100%.
[0061] Wet sieve residue test: Take 10.0g of sample, dilute it 100 times with standard water and pass it through a 75μm test sieve. Wash the residue on the sieve and dry it at 60℃ to constant weight. The wet sieve residue is calculated as the mass of the material on the sieve after drying relative to the mass of the original sample.
[0062] Persistent foam volume test: Take 1.0g of sample, add standard water to make up to 100mL, place it in a stoppered graduated cylinder, invert it 30 times, let it stand for 1min and then read the volume of the foam layer.
[0063] Thermal storage stability test: Before thermal storage, the D90, suspension rate, and wet sieve residue of the samples were measured. The samples were sealed and stored at 54℃ for 14 days, then removed and allowed to return to room temperature. The D90, suspension rate, and wet sieve residue were measured again, and the appearance of the samples after thermal storage was observed. The D90 growth rate after thermal storage was calculated using the following formula: The percentage increase of D90 after thermal storage is calculated as follows: (D90 after thermal storage - D90 before thermal storage) ÷ D90 before thermal storage × 100%.
[0064] Cold storage stability test: After sealing the sample, it was stored at 0℃ for 7 days. After being taken out and restored to room temperature, the crystallization, agglomeration, stratification and redispersion states were recorded respectively.
[0065] Hard water dilution stability test: The sample was diluted 500 times with standard hard water with a hardness of 500 mg / L (calculated as calcium carbonate). After standing for 2 hours, the flocculation and sedimentation states were observed. The D90 particle size growth rate of solid particles in the diluted solution was measured, and the residue on the sieve after hard water dilution was determined. The D90 growth rate after hard water dilution was calculated using the following formula: The percentage increase of D90 after dilution of hard water is calculated as follows: (D90 after standing for 2 hours - initial D90) ÷ initial D90 × 100%.
[0066] Hard water dilution residue / % = Mass of residue on a 75μm test sieve after drying ÷ Mass of the original sample used to prepare the diluent × 100%.
[0067] Table 11 Initial physical and chemical properties Example 1 7.0 4.8 91.0 0.082 3.1 Example 2 7.1 4.2 93.8 0.058 2.6 Example 3 7.1 3.5 94.7 0.040 2.0 Example 4 7.2 3.9 94.3 0.052 2.4 Example 5 7.2 4.6 92.5 0.071 2.9 Example 6 7.1 4.0 93.6 0.049 2.2 Example 7 7.1 3.4 95.1 0.043 2.3 Example 8 7.1 3.8 94.7 0.047 2.0 Example 9 7.2 4.3 93.1 0.064 2.5 Example 10 7.1 3.6 94.4 0.042 1.7 Example 11 7.1 3.7 95.0 0.046 1.5 Example 12 7.1 4.0 93.9 0.056 2.4 Example 13 7.1 3.6 95.2 0.039 2.1 Example 14 7.2 3.9 93.7 0.061 2.2 Example 15 7.1 3.3 95.8 0.038 2.2 Example 16 7.1 3.1 95.7 0.033 1.9 Example 17 7.2 3.4 95.4 0.036 2.1 Example 18 7.1 3.5 94.8 0.041 2.4 Example 19 7.1 3.3 95.2 0.044 2.0 Example 20 7.2 3.4 95.0 0.039 2.2 Comparative Example 1 7.0 6.8 82.6 0.185 3.9 Comparative Example 2 7.0 6.1 85.2 0.148 3.6 Comparative Example 3 7.1 4.2 91.5 0.073 8.2 Comparative Example 4 7.2 5.5 87.1 0.126 4.6 Table 12 Storage and Hard Water Dilution Stability Example 1 17.8 87.4 0.121 Slight settling, can be redispersed after shaking. No crystallization, no agglomeration, slight sedimentation allows for redispersibility 24.2 0.132 Example 2 14.6 90.5 0.091 No obvious stratification; can be redispersed after shaking. No crystallization, no agglomeration, redispersible 20.5 0.107 Example 3 11.2 93.1 0.069 No obvious stratification, can be further dispersed No crystallization, no agglomeration, redispersible 18.0 0.093 Example 4 12.9 92.0 0.081 No obvious stratification, can be further dispersed No crystallization, no agglomeration, redispersible 19.6 0.101 Example 5 16.1 89.4 0.107 Slight settling, can be redispersed after shaking. No crystallization, no agglomeration, slight sedimentation allows for redispersibility 22.1 0.118 Example 6 13.7 91.8 0.078 No obvious stratification, can be further dispersed No crystallization, no agglomeration, redispersible 20.1 0.104 Example 7 10.4 93.4 0.066 No obvious stratification, can be further dispersed No crystallization, no agglomeration, redispersible 17.3 0.089 Example 8 12.1 92.6 0.075 No obvious stratification, can be further dispersed No crystallization, no agglomeration, redispersible 18.7 0.099 Example 9 15.3 90.7 0.094 Slight settling, can be redispersed after shaking. No crystallization, no agglomeration, redispersible 21.4 0.111 Example 10 11.8 93.0 0.068 No obvious stratification, can be further dispersed No crystallization, no agglomeration, redispersible 18.2 0.086 Example 11 10.9 93.6 0.063 No obvious stratification, can be further dispersed No crystallization, no agglomeration, redispersible 18.9 0.092 Example 12 14.2 91.4 0.087 Slight settling, can be redispersed after shaking. No crystallization, no agglomeration, redispersible 20.7 0.109 Example 13 10.7 93.3 0.065 No obvious stratification, can be further dispersed No crystallization, no agglomeration, redispersible 17.8 0.097 Example 14 13.4 91.6 0.085 Slight settling, can be redispersed after shaking. No crystallization, no agglomeration, redispersible 19.9 0.103 Example 15 9.1 94.0 0.060 No obvious stratification, can be further dispersed No crystallization, no agglomeration, redispersible 16.2 0.075 Example 16 9.6 93.8 0.056 No obvious stratification, can be further dispersed No crystallization, no agglomeration, redispersible 14.9 0.082 Example 17 10.0 94.1 0.062 No obvious stratification, can be further dispersed No crystallization, no agglomeration, redispersible 15.8 0.078 Example 18 10.3 93.2 0.064 No obvious stratification, can be further dispersed No crystallization, no agglomeration, redispersible 11.8 0.052 Example 19 10.6 93.5 0.058 No obvious stratification, can be further dispersed No crystallization, no agglomeration, redispersible 9.3 0.049 Example 20 10.8 93.4 0.067 No obvious stratification, can be further dispersed No crystallization, no agglomeration, redispersible 10.7 0.057 Comparative Example 1 34.1 77.8 0.291 Significant settling and prolonged redispersion time No crystallization occurred, but sedimentation was observed, and redispersibility after shaking was slow. 39.0 0.255 Comparative Example 2 27.9 80.6 0.229 Significant settling and prolonged redispersion time No crystallization occurred, but sedimentation was observed, and redispersibility after shaking was slow. 34.2 0.225 Comparative Example 3 17.2 88.8 0.121 There is a lot of foam on the surface, which can be redispersed after shaking. No crystallization, no agglomeration, redispersible 22.7 0.119 Comparative Example 4 24.1 82.4 0.203 Slight stratification, can be redispersed after shaking. No crystallization, slight stratification, redispersible 31.0 0.188 As shown in Tables 11 and 12, Examples 1-5 all successfully formed suspension formulations of flonicamid and spirotetramat. Example 3 showed a more balanced performance in terms of particle size, suspension rate, wet sieve residue, persistent foam amount, D90 growth rate after heat storage, and stability after hard water dilution. Compared with Example 3, Comparative Example 1 removed the modified nanocellulose stabilizer, and Comparative Example 2 used unmodified nanocellulose to replace the stabilizer. Both showed increased particle size and wet sieve residue, decreased suspension rate, and worsened stability after heat storage and hard water dilution. This indicates that modified nanocellulose with both carboxyl and sulfonate groups is beneficial for improving the dispersion stability of the active ingredient particles in the aqueous phase. Comparative Example 3 removed the defoaming interface regulating component, resulting in increased persistent foam amount and more surface foam after heat storage. This indicates that the composite component of aminosilane-modified silica and polyether-modified siloxane is beneficial for regulating foam during milling and storage. Comparative Example 4 uses a commonly used dispersion stabilization system, and its suspension rate, particle size control, thermal storage stability, and hard water dilution stability are weaker than those of Example 3, indicating that the functionalized stabilization system of this application is more suitable for the processing and storage requirements of high-content dual-pharmaceutical suspensions.
[0068] Tables 11 and 12 show that the modified nanocellulose stabilizers obtained in Examples 3 and 6-9 were prepared under different conditions. Example 7 had an initial D90 of 3.4 μm, a suspension rate of 95.1%, a D90 increase rate of 17.3% after dilution in hard water, and a D90 increase rate of 10.4% after heat storage. Its overall performance was better than most samples in this group, indicating that the degree of carboxylation, the amount of sulfonate monomer, and the graft polymerization conditions corresponding to Preparation Example 3 were more suitable for maintaining the dispersion state of the dual-origin particles after processing, storage, and dilution in hard water. The persistent foam volume of this sample was 2.3 mL, which is still at a low level, indicating that changes in the source of the modified nanocellulose mainly affected the particle dispersion stability and the state after dilution in hard water.
[0069] As shown in Tables 11 and 12, Examples 7 and 10-11 used defoaming interface conditioning components from different sources. Compared with Example 7, the amount of persistent foam in Examples 10 and 11 decreased from 2.3 mL to 1.7 mL and 1.5 mL, respectively, while the initial D90, suspension rate, and wet sieve residue remained within a relatively close range. Example 11 had a lower amount of persistent foam, with a D90 growth rate of 10.9% after heat storage and a wet sieve residue of 0.063% after heat storage, indicating that the defoaming interface conditioning component obtained in Preparation Example 8 is more suitable for this suspension formulation system in terms of foam control and maintenance of interface state after heat storage.
[0070] As shown in Tables 11 and 12, under the condition that the shearing speed and shearing time remain consistent, Examples 12-14 used modified nanocellulose pre-dispersion liquid-solid contents of 3%, 5%, and 8%, respectively. Example 13 had an initial D90 of 3.6 μm, a suspension rate of 95.2%, a D90 increase rate of 10.7% after heat storage, and a wet sieve residue of 0.065% after heat storage. These results were relatively uniform in this group of samples, indicating that under the process conditions, a pre-dispersion liquid-solid content of 5% is more conducive to the uniform dispersion of modified nanocellulose in the aqueous phase.
[0071] As shown in Tables 11 and 12, Examples 15-17 introduced different amphiphilic carboxylic acid-sulfonate comb-shaped dispersants based on the pre-dispersion process of Example 13. Compared with Example 13, the initial D90 of Examples 15-17 decreased from 3.6 μm to 3.1-3.4 μm, and the wet sieve residue remained in a low range of 0.033-0.038%, indicating that the comb-shaped dispersant, as part of the dispersing and wetting agent, is beneficial to improving the wetting and adsorption of the two active ingredients on the surface of the particles and the particle size retention after sand milling. Among them, the initial D90 of Example 16 was 3.1 μm, and the wet sieve residue was 0.033%, showing that the comb-shaped dispersant obtained in Preparation Example 10 has a good wetting and dispersing effect in this formulation.
[0072] As shown in Tables 11 and 12, Examples 18-20 introduced different hard water dilution anti-flocculation crosslinking polymer stabilizers based on the comb-shaped dispersant source of Example 16. Compared with Example 16, the D90 growth rate after hard water dilution in Examples 18-20 decreased from 14.9% to 9.3-11.8%, and the hard water dilution sieve residue decreased from 0.082% to 0.049-0.057%, indicating that the crosslinking polymer stabilizer, as part of the auxiliary stabilizer, can further improve the anti-flocculation state after hard water dilution. Among them, the D90 growth rate after hard water dilution in Example 19 was 9.3%, and the hard water dilution sieve residue was 0.049%, indicating that the crosslinking polymer stabilizer obtained in Preparation Example 13 has a good inhibitory effect on particle bridging flocculation caused by calcium and magnesium ions in hard water.
[0073] The above are all preferred embodiments of this application and are not intended to limit the scope of protection of this application. All equivalent changes made to the structure, composition, and principle of this application should be covered within the scope of protection of this application.
Claims
1. A suspension formulation of flonicamid and spirotetramat, characterized in that, The composition, by weight percentage, includes 14-18% flonicamid, 20-28% spirotetramat, 5-10% dispersant and wetting agent, 0.5-2% auxiliary stabilizer, 0.2-2.5% modified nanocellulose stabilizer (based on effective solids), 3-7% antifreeze, 0.1-0.5% preservative, 0.05-0.8% defoaming interface conditioning component, with the balance made up to 100% by water. The modified nanocellulose stabilizer is nanocellulose with both carboxyl and sulfonate groups on its surface.
2. The suspension formulation of flonicamid and spirotetramat according to claim 1, characterized in that, The dispersing and wetting agent includes an amphiphilic carboxylic acid-sulfonate comb-shaped dispersant, which is a water-dispersible polymer formed by copolymerization of a carboxyl-containing alkenyl monomer or its salt, an alkenyl monomer containing a sulfonate group, a polyether side chain monomer, and a hydrophobic anchoring monomer.
3. The suspension formulation of flonicamid and spirotetramat according to claim 2, characterized in that, When preparing the amphiphilic carboxylic acid-sulfonate comb-shaped dispersant, the molar ratio of the carboxyl-containing alkenyl monomer or its salt, the alkenyl monomer containing sulfonate groups, the polyether side chain monomer, and the hydrophobic anchoring monomer is 1:(0.2-1.5):(0.5-3):(0.05-0.8).
4. The suspension formulation of flonicamid and spirotetramat according to claim 1, characterized in that, The modified nanocellulose stabilizer was prepared by the following method: (1) Nanocellulose is oxidized by TEMPO or carboxymethylated to obtain carboxylated nanocellulose; (2) Disperse the carboxylated nanocellulose in water, purge it with an inert gas, add a persulfate initiator and an alkenyl monomer containing a sulfonate group, and carry out graft polymerization at 60-70°C for 3-5 hours; (3) After grafting polymerization, the modified nanocellulose stabilizer is obtained by centrifugation, washing, ultrafiltration or dialysis, and adjustment of solid content.
5. The suspension formulation of flonicamid and spirotetramat according to claim 4, characterized in that, The alkenyl monomer containing sulfonate groups includes one or more of 2-acrylamido-2-methylpropanesulfonate, vinyl sulfonate, and styrene sulfonate.
6. The suspension formulation of flonicamid and spirotetramat according to claim 1, characterized in that, The defoaming interface regulating component includes aminosilane-modified silica and polyether-modified siloxane, wherein the mass ratio of aminosilane-modified silica to polyether-modified siloxane is 1:(0.3-3).
7. The suspension formulation of flonicamid and spirotetramat according to claim 6, characterized in that, The defoaming interface conditioning component is prepared by the following method: (1) Surface treatment of silica with aminosilane to obtain aminosilane modified silica; wherein the aminosilane includes one or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and N-aminoethyl-3-aminopropyltrimethoxysilane; (2) The aminosilane-modified silica and polyether-modified siloxane are mixed and dispersed to obtain the defoaming interface regulating component.
8. The suspension formulation of flonicamid and spirotetramat according to claim 1, characterized in that, The auxiliary stabilizer includes a hard water-dilutable anti-flocculation crosslinking polymer stabilizer, which is a water-dispersible crosslinking polymer containing carboxylate structural units, sulfonate structural units, and polycarboxyl structural units formed from polymerizable monomers containing polycarboxyl groups.
9. The suspension formulation of flonicamid and spirotetramat according to claim 8, characterized in that, The hard water dilution anti-flocculation crosslinking polymer stabilizer is prepared by the following method: (1) Disperse carboxyl-containing alkenyl monomers or their salts, alkenyl monomers containing sulfonate groups, polymerizable monomers containing multiple carboxyl groups, and crosslinking monomers in water to obtain an aqueous monomer phase; (2) Under inert gas protection, a persulfate-bisulfite redox initiation system is added to the aqueous phase of the monomer and reacted at 35-60℃ for 2-5 hours. The mixture is then filtered through a 100μm filter and the effective solid content of the crosslinked polymer is adjusted to obtain the hard water diluted antiflocculation crosslinked polymer stabilizer.
10. A method for preparing a suspension formulation of flonicamid and spirotetramat according to any one of claims 1-9, characterized in that, Includes the following steps: (1) Water, dispersant, wetting agent, auxiliary stabilizer, antifreeze agent and modified nanocellulose stabilizer are mixed to obtain a dispersed and stable aqueous phase; (2) Flupyradifurone technical and spirotetramat technical were added to the dispersed and stable aqueous phase under stirring conditions, and shear dispersion was carried out to obtain a pre-dispersed slurry; (3) The pre-dispersed slurry is subjected to sand milling, preservatives and defoaming interface conditioning components are added, and water is added to make up the difference, so as to obtain the flonicamid and spirotetramat suspension preparation.